Discrepancy of PCR and serologic test on genital herpes: a case report - Fadhilla, Jhauharina Rizki (Bali Dermatology and Venereology Journal, 2021)
Background: Laboratory investigation for genital herpes (GH) includes serologic tests and polymerase chain reaction (PCR) with different sensitivity and specificity; occasionally, the results are not conclusive. Clinical symptoms are often atypical. We report a case of GH in HIV-infected patients with a non-reactive serologic test but positive PCR.Case Description: A 29-years old HIV-positive man presented with multiple painful shallow ulcers with pus on his penis in the last five days. PCR examination showed a positive result, whereas anti-HSV 1 IgM, anti-HSV 2 IgM, anti-HSV 2 IgG, VDRL, and TPHA were negative. The anti-HSV- 1 IgG result was reactive with a CD4 value of 122 cells/Î¼L. The patient was given Acyclovir 3x400 mg for ten days and Co-amoxiclav 3x625 mg for seven days. Significant improvement was obtained, and the pain subsided.Conclusion: Clinical features of GH in infected HIV patients are often atypical and resemble other genital ulcers, thus requiring additional investigations. The serologic test may sometimes present a false negative, whereas PCR is much more sensitive and specific, nearing 100%. In patients with HIV infection, GH diagnosis at an early stage can shorten the course of the disease and prevent complications.